Analysis Of The Determination Of Production Costi In The Sumedang Hybrid Tofu Factory Business In Bengkulu City - Juniar, Intan; Herlin, Herlin; Putra , Iswidana Utama (Utami Publisher, 2025)
Cost of Goods Sold (COGS) is the total cost incurred by a company to acquire and process raw materials into finished products. These costs include raw material costs, labor costs, and factory overhead costs, all of which are listed in the report. The purpose of this study is to determine and analyze the process of determining the cost of goods produced at Tofu Sumedang Hybrid in Bengkulu City using full costing and its accuracy in reflecting actual costs. The methods used in this study are observation, interviews, and documentation based on the calculation of the cost of goods sold (COGS) conducted by the Sumedang Hibrida Tofu business in Bengkulu City using the simple method, the COGS was Rp 125,000,000 for the period May to August 2025, with 1,250 orders. This calculation does not include all overhead cost components in detail. Using the full costing method, which comprehensively calculates all production cost components, including direct materials, direct labor, and fixed and variable factory overhead, the COGS was Rp 167,600,000 for the same period.